2009
DOI: 10.1111/j.1365-2125.2008.03344.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the haplotypes of the human pregnane X receptor gene on the basal and St John's wort‐induced activity of cytochrome P450 3A4 enzyme

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Human pregnane X receptor (PXR/NR1I2) is a key regulator of cytochrome P450 3A4. • To date, there are 198 reported SNPs for the human PXR/NR1I2 gene.• Some of these SNPs are found to affect the inducing ability of PXR to CYP3A4. WHAT THIS STUDY ADDS• This study, for the first time, has investigated the effect of PXR haplotype on basal and St John's wort-induced CYP3A4 activity in humans.• H1/H1 of the PXR gene had weaker basal transcriptional activity but greater induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Higher mRNA levels of intestinal CYP3A4 were associated with g.7635G and g.8055T, and greater induction of CYP3A activity was found in Ϫ25385TT subjects than in Ϫ25385CC subjects, as measured by an erythromycin breath test (Zhang et al, 2001). In addition, a recent report showed that the NR1I2 haplotype, including TGT, was associated with weaker basal activity but greater inducible transcriptional activity of CYP3A4, based on a PK study of nifedipine (Wang et al, 2009). However, these studies were performed with CYP3A4 substrates, a very small sample size (n ϭ 3), and limited in vivo PK information regarding the substrate drugs, and, in addition, their associated mechanism has not been experimentally demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher mRNA levels of intestinal CYP3A4 were associated with g.7635G and g.8055T, and greater induction of CYP3A activity was found in Ϫ25385TT subjects than in Ϫ25385CC subjects, as measured by an erythromycin breath test (Zhang et al, 2001). In addition, a recent report showed that the NR1I2 haplotype, including TGT, was associated with weaker basal activity but greater inducible transcriptional activity of CYP3A4, based on a PK study of nifedipine (Wang et al, 2009). However, these studies were performed with CYP3A4 substrates, a very small sample size (n ϭ 3), and limited in vivo PK information regarding the substrate drugs, and, in addition, their associated mechanism has not been experimentally demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The CAC haplotype was the most common and was regarded as the wild-type allele, and the CGT and TGT haplotypes were the primary variant alleles, based on their allele frequencies. Considering that the Ϫ25385CϾT SNP has been reported previously to exhibit altered transcriptional activity (Zhang et al, 2001;Wang et al, 2009), the subjects were divided into TGT carrier (n ϭ 13) and noncarrier (n ϭ 22) groups, based on the existence of the NR1I2 TGT haplotype, as well as the Ϫ25385CϾT SNP.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical evidence suggests that St. John’s wort may cause both pharmacokinetic and pharmacodynamic interactions. Using well-established probe drugs, a great number of clinical trials have consistently shown that St. John’s wort induced P-glycoprotein as well as CYP3A4, CYP2E1 and CYP2C19, with no effect on CYP1A2, CYP2D6 or CYP2C9 [144,145,146,147,148,149,150,151,152,153,154,155,156,157]. Induction of CYP enzymes and P-glycoprotein is caused by hyperforin via activation of the pregnane X receptor [158,159,160,161].…”
Section: Clinical Interactions Between Herbs and Conventional Drugsmentioning
confidence: 99%
“…Conversely to carboplatin, paclitaxel exhibits an extensive hepatic metabolism involving phase I enzymes (CYP1B1, CYP3A4, CYP3A5, CYP2C8) and transporters (SLCO1B3, ABCB1, ABCC1, ABCC2) [7,8]. SNPs from the nuclear receptors CAR (NR1I3) and PXR (NR1I2) were also selected because of the crucial role of these genes as ligand-dependent transcription Polymorphisms in SLCO1B3 and NR1I2 as genetic determinants of hematotoxicity of carboplatin and paclitaxel combination 10.2217/PGS. 15.84 Pharmacogenomics (Epub ahead of print) future science group Research Article Mbatchi, Schmitt, Thomas et al factors regulating the expression of many drug-metabolizing enzymes and transporters [9].…”
Section: Introductionmentioning
confidence: 99%